The effect of students’ perception of using teaching media and vocabulary mastery on students’ listening skill - Lilik Yuliawati; Endang Sri Andayani; Aprillia Aprillia (English Teaching Journal : A Journal of English Literature, Language and Education, 2020)
This research aimed to analyze the effect of students’ perception of using teaching media and vocabulary mastery on students’ listening skill. The method used in this research was survey with double regression technique. It was conducted at a Private Vocational School in North Jakarta. The numbers of the samples were 60 students. The researchers got the data from the questionnaire by using Likert Scale. The result of this research showed that: 1) There is a significant effect of students’ perception of teaching media and vocabulary mastery jointly on students’ listening skill; 2) There is a significant effect of students’ perception of teaching media on students’ listening skill; 3) There is a significant effect of vocabulary mastery on students’ listening skill.